Time-Resolved Perfusion Imaging at the Angiography Suite: Preclinical Comparison of a New Flat-Detector Application to Computed Tomography Perfusion. Issue 2 (February 2015) - Jürgens, Julian H.W.; Schulz, Nadine; Wybranski, Christian; Seidensticker, Max; Streit, Sebastian; Brauner, Jan; Wohlgemuth, Walter A.; Deuerling-Zheng, Yu; Ricke, Jens; Dudeck, Oliver
Abstract : Objectives: The objective of this study was to compare the parameter maps of a new flat-panel detector application for time-resolved perfusion imaging in the angiography room (FD-CTP) with computed tomography perfusion (CTP) in an experimental tumor model. Materials and Methods: Twenty-four VX2 tumors were implanted into the hind legs of 12 rabbits. Three weeks later, FD-CTP (Artis zeego; Siemens) and CTP (SOMATOM Definition AS +; Siemens) were performed. The parameter maps for the FD-CTP were calculated using a prototype software, and those for the CTP were calculated with VPCT-body software on a dedicated syngo MultiModality Workplace. The parameters were compared using Pearson product-moment correlation coefficient and linear regression analysis. Results: The Pearson product-moment correlation coefficient showed good correlation values for both the intratumoral blood volume of 0.848 ( P < 0.01) and the blood flow of 0.698 ( P < 0.01). The linear regression analysis of the perfusion between FD-CTP and CTP showed for the blood volume a regression equation y = 4.44x + 36.72 ( P < 0.01) and for the blood flow y = 0.75x + 14.61 ( P < 0.01). Conclusions: This preclinical study provides evidence that FD-CTP allows a time-resolved (dynamic) perfusion imaging of tumors similar to CTP, which provides the basis for clinical applications such as the assessment of tumor response to locoregional therapies directly in the angiography suite.